Hintikka’s Interrogative Model and a Logic of Discovery and Justification - Arto Mutanen (Acta Baltica Historiae et Philosophiae Scientiarum, 2015)
The relationship between discovery and justification is not clear. According to a standard twentieth-century opinion, in the philosophy of science these two are understood as separate problems: how to recognize and conceptualize the object of study and how to find the justification for the conceptualized belief. How to study the logic of discovery? What kind of logic might such a logic be? The basic observation is that discoveries do not take place in a vacuum. They have to be localized into scientific inquiry processes: a discovery is a discovery only in the context of a scientific inquiry process. To do this we use a systematic logico-philosophical model called the interrogative model of inquiry, which was developed by Jaakko Hintikka. The interrogative model of inquiry allows us to consider the scientific inquiry process as a strategic, goal-tracking process which gives justification for the discovery. The model allows us to formulate a systematic logic of scientific discovery and justification.